ATTEMPTS TO IMPROVE HOSPITAL PREPAREDNESS IN DEALING WITH THE COVID-19 PANDEMIC - Inge Dhamanti; Ida Nurhaida; Taufik Rachman; Rosediani Muhamad (Universitas Airlangga, 2022)
The rapid development of the corona virus has caused many positive cases to be confirmed both globally and nationally. The development of COVID-19 cases that continues to grow requires every hospital to always strive to improve hospital preparedness. One of the tools that can be used to improve hospital preparedness is the Rapid Hospital Readiness Checklist developed by WHO. Based on the background of this community service activity, it aims to assist hospitals in conducting self-assessment through the development of applications related to hospital preparedness in the face of the COVID-19 pandemic. This community service method is divided into two, namely, Focus Group Discussion (FGD) which aims to obtain information needed for application development and socialization which aims to practice application use. The presence of this application was welcomed by hospitals and related service units because it can help make it easier to fill out a checklist related to hospital preparedness. So with this application, it is hoped that it can help hospitals and stakeholders in efforts to improve hospital preparedness.